Strategi Meningkatkan Brand Awareness Melalui Konten Kreatif Dalam Pemasaran Media Sosial Tiktok Brand Tenue De Attire - Erwin Permana; Dewi Stalastiana; Rahil Khalisoh; Syamsurizal Syamsurizal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The increasingly massive use of social media has opened up opportunities for the development of the business sector. This reality also provides opportunities for the growth and development of local products. One local brand that has developed quite well by utilizing social media, especially TikTok, is the Tenue de Attire brand. This research aims to analyze strategies for increasing brand awareness through creative content in TikTok Brand Tenue de Attire social media marketing. This research uses a descriptive qualitative approach, data was obtained using literature review techniques and official publications. Tenue De Attire's marketing strategy shows that they can use social media, especially TikTok, to increase brand awareness and introduce their products to the public. They managed to create a strong connection between the audience and the brand by focusing on creating engaging video content, especially by using adaptable ideas and following popular trends. Tenue De Attire uses an Inbound Marketing approach to direct TikTok users from the stage of attracting attention to the stage of becoming potential customers, by using interesting content to provide information about their products indirectly. Inbound marketing strategy has four stages, namely: Attract, Convert, Close and Delight. Using TikTok's Shop and Live features also helped them increase customer relations and sales. Therefore, Tenue De Attire has achieved success thanks to its innovative and smart marketing strategies.